Ruang Lingkup Ekonomi dalam Perspektif Islam - Ash-Shiddiqy, Muhammad (LPTNU Sumenep, 2023)
The scope of Islamic Economics is essentially the same as the traditional financial scope that we have recognised thus far. however, there are some of variations in concepts that consist of, among others, the prohibition of usury, playing, and uncertainty in transactions. The simple philosophy of economics, both traditional and monetary in Islam, prohibits flowering of money. but, conventional economics then deviates in this regard. Islamic economics is built on the idea of Islam, consequently it is an crucial a part of the faith of Islam. Islamic economics follows Islamic faith in various factors, and is an embodiment of financial conduct based on Islamic teachings which incorporates a way to view financial troubles, analyze, and endorse alternative answers to numerous economic problems. Islamic monetary scope consists of its history, muamalah fiqh, social machine, fundamental policies( which include zakat, infaq, waqf, prohibiting maisir, gharar, and usury), including macroeconomic elements, authorities rules( regulator) in its development, and additionally the system recording( accounting) that ought to be used.